1992
DOI: 10.1152/ajpheart.1992.262.4.h999
|View full text |Cite
|
Sign up to set email alerts
|

Importance of charge on transvascular albumin transport in skin and skeletal muscle

Abstract: To test the hypothesis that charge affects the transvascular transport of albumin, the tracer clearance for albumin and a set of charge-modified albumins was measured in heel skin and gastrocnemius muscle from anesthetized rabbits. The charge on albumin was made less negative by modifying the carboxyl groups of aspartic and glutamic acids to alcohol groups. Four preparations of modified albumin having isoelectric points of 5.1 +/- 0.4, 5.8 +/- 0.4, 7.1 +/- 0.5, and 8.1 +/- 0.7 were studied. In skin, the cleara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…The charge-dependence in vascular permeability in tumours is consistent with observations in normal tissues (Jain, 1997;Curry et al, 1987;Turner et al, 1983;Vehaskari et al, 1984;Deen et al, 1980;Baldwin et al, 1991;Dermietzel et al, 1983;Adamson et al, 1988;Barrowcliffe et al, 1990;Gandhi and Bell, 1992;Gilchrist and Parker, 1985;Haraldsson et al, 1983;Khaw et al, 1991;Leypoldt and Henderson, 1993;Michel and Phillips, 1985;Öjteg et al, 1987;Parker et al, 1985;Rasio and Goresky, 1985;Triguero et al, 1989), suggesting the luminal surface of tumour vascular endothelium is negatively charged as well.…”
Section: Molecular Charge-dependence Of Vascular Permeabilitysupporting
confidence: 82%
See 1 more Smart Citation
“…The charge-dependence in vascular permeability in tumours is consistent with observations in normal tissues (Jain, 1997;Curry et al, 1987;Turner et al, 1983;Vehaskari et al, 1984;Deen et al, 1980;Baldwin et al, 1991;Dermietzel et al, 1983;Adamson et al, 1988;Barrowcliffe et al, 1990;Gandhi and Bell, 1992;Gilchrist and Parker, 1985;Haraldsson et al, 1983;Khaw et al, 1991;Leypoldt and Henderson, 1993;Michel and Phillips, 1985;Öjteg et al, 1987;Parker et al, 1985;Rasio and Goresky, 1985;Triguero et al, 1989), suggesting the luminal surface of tumour vascular endothelium is negatively charged as well.…”
Section: Molecular Charge-dependence Of Vascular Permeabilitysupporting
confidence: 82%
“…Thus, it restricts the extravasation of anionic macromolecules, as has been demonstrated in cultured endothelial cell monolayer (Sahagun et al, 1990) and various normal tissues (Jain, 1997;Curry et al, 1987;Turner et al, 1983;Vehaskari et al, 1984;Deen et al, 1980;Baldwin et al, 1991;Dermietzel et al, 1983;Adamson et al, 1988;Barrowcliffe et al, 1990;Gandhi and Bell, 1992;Gilchrist and Parker, 1985;Haraldsson et al, 1983;Khaw et al, 1991;Leypoldt and Henderson, 1993;Michel and Phillips, 1985;Öjteg et al, 1987;Parker et al, 1985;Rasio and Goresky, 1985;Triguero et al, 1989). Adamson et al (1988) have demonstrated that the microvascular permeability to α-lactalbumin (M r = 14 176, net charge -10) is approximately 50% of that to ribonuclease (M r = 13 683, net charge +4), suggesting that the microvascular permeability to the positively charged molecules is higher than the permeability to the negative ones.…”
mentioning
confidence: 96%
“…In skeletal muscle, the clearance for the most neutral modified albumins and cationic albumins was found to be 50 and 150% greater than that for native albumin, respectively. This clearly shows that charge affects the transvascular transport of albumin (35,36). In this study, the fusion has been carried out through the N-and C-terminals.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in experiments in pulmonary tissue, the EC affinity for anionic albumin was significantly enhanced by neutralization of the anionic glycocalycal charge by protamine sulfate treatment [148]. In another study, anionic albumin was catonized by modification of carboxyl residues, which resulted in an 80% increase in EC binding of cat-albumin in skeletal muscle [53]. No examples exist of similar approaches being effective in the CNS vasculature.…”
Section: Exploiting Spinal Microvascular Ec Reactivity For Therapeutimentioning
confidence: 99%